2021
DOI: 10.1177/0363546521996389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Tunnel Widening On the Outcomes of a Single Stage–Only Approach to Every Revision Anterior Cruciate Ligament Reconstruction: An Analysis of 409 Consecutive Patients From the SANTI Study Group

Abstract: Background: Preoperative tunnel widening is a frequently reported indication for performing a 2-stage revision anterior cruciate ligament reconstruction (ACLR) instead of a single-stage procedure. However, the strength of the available evidence to support a 2-stage strategy is low. Purpose/Hypothesis: The purpose was to evaluate the clinical outcomes of a single stage–only approach to revision ACLR. It was hypothesized that this approach would be associated with significant improvements from baseline in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Relatively little prior work has evaluated the relationship between prior tunnel size and outcomes of revision ACLR. The only previous study in the area, published by the SANTI group from France in 2021, 28 compared graft failure risk and patient-reported outcomes based on prior tunnel size at a mean of 5.9 years postoperatively. They defined the enlarged tunnel group as having either a femoral or tibial tunnel larger than 12 mm and noted no difference failure risk or patient-reported outcomes based on tunnel size.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little prior work has evaluated the relationship between prior tunnel size and outcomes of revision ACLR. The only previous study in the area, published by the SANTI group from France in 2021, 28 compared graft failure risk and patient-reported outcomes based on prior tunnel size at a mean of 5.9 years postoperatively. They defined the enlarged tunnel group as having either a femoral or tibial tunnel larger than 12 mm and noted no difference failure risk or patient-reported outcomes based on tunnel size.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al even reported greater widening when bioabsorbable interference screws were used [ 29 ]. Finally, Pioger et al showed no influence of tunnel widening on the surgical management of revision ACLR [ 30 ]. Single-stage management has always been possible using an outside-in femoral guide, and excellent clinical outcomes have thus been obtained independently of preoperative tunnel position and width.…”
Section: Discussionmentioning
confidence: 99%
“…Pioger et al. [ 7 ] evaluated 409 revisions performed in a single stage. The femoral tunnel was drilled with the outside-in technique, with no major technical problems and no need to perform the procedure in two stages.…”
Section: Introductionmentioning
confidence: 99%